2021
DOI: 10.1002/jhbp.993
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA as a predictive marker for occult metastases in pancreatic cancer patients with radiographically non‐metastatic disease

Abstract: Purpose To elucidate the effectiveness of circulating tumor DNA (ctDNA) for predicting occult metastases in patients with pancreatic cancer without apparent metastases. Methods Circulating tumor DNA was obtained from plasma samples of 165 patients with pancreatic cancer and analyzed using droplet digital PCR. The prevalence and allele frequencies of ctDNA were compared across different patterns and degrees of metastatic spread. Results Of the 142 patients without apparent metastases who underwent abdominal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Novel biomarkers such as circulating tumor cells (CTCs) and cell‐free DNA (cfDNA) have been developed recently. 28 , 29 However, research on CTCs and cfDNA remains in the experimental stage, warranting future large trials. The levels of CTCs in peripheral blood are low; therefore, their detection is extremely challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel biomarkers such as circulating tumor cells (CTCs) and cell‐free DNA (cfDNA) have been developed recently. 28 , 29 However, research on CTCs and cfDNA remains in the experimental stage, warranting future large trials. The levels of CTCs in peripheral blood are low; therefore, their detection is extremely challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the only noninvasive blood‐based biomarker routinely used is CA19‐9. Novel biomarkers such as circulating tumor cells (CTCs) and cell‐free DNA (cfDNA) have been developed recently 28,29 . However, research on CTCs and cfDNA remains in the experimental stage, warranting future large trials.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Hata et al 121 studied circulating tumor DNA to observe its correlation with patterns of metastatic spread. They found not only a remarkably high prevalence of circulating tumor DNA in patients with evident radiographic metastases but also a significantly higher prevalence in patients with occult disease not initially seen on imaging 121 . In 2020, Nicolle et al 122 presented GemPred , a RNA-based whole transcriptome signature that was shown to act as a predictor of tumor sensitivity for patients receiving gemcitabine.…”
Section: Markers Of Treatment Response To Nat In Pdacmentioning
confidence: 99%
“…120 This study concluded that the preoperative number of CTCs was the only predictor for recurrence of malignancy within 12 months of resection. In 2021, Hata et al 121 studied circulating tumor DNA to observe its correlation with patterns of metastatic spread. They found not only a remarkably high prevalence of circulating tumor DNA in patients with evident radiographic metastases but also a significantly higher prevalence in patients with occult disease not initially seen on imaging.…”
Section: Markers Of Treatment Response To Nat In Pdacmentioning
confidence: 99%
See 1 more Smart Citation